2019
DOI: 10.1021/acs.nanolett.9b04369
|View full text |Cite
|
Sign up to set email alerts
|

Diels–Alder Reactions in Water Are Determined by Microsolvation

Abstract: Nanoconfined aqueous environments and the recent advent of accelerated chemistry in microdroplets are increasingly being investigated for catalysis. The mechanisms underlying the enhanced reactivity in alternate solvent environments, and whether the enhanced reactivity due to nanoconfinement is a universal phenomenon, are not fully understood. Here, we use ab initio molecular dynamics simulations to characterize the free energy of a retro-Diels-Alder reaction in bulk water at very different densities and in wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 47 publications
3
48
0
Order By: Relevance
“…In addition to experiments, modelling the kinetics of reactions within droplets and at interfaces can help clarify our understanding of the mechanisms leading to reaction acceleration in micro-and nano-compartments. A few recent examples of such contributions include the kinetic modelling of reactions in microemulsions, 60 molecular dynamics simulations of a cycloaddition reaction at the water-graphene interface, 110 quantum mechanical calculations of the energies of desolvated molecules at the water-vacuum interface 61 and estimation of the magnitude of electric elds in microdroplets. 73 Finally, there is an important distinction between two different objectives that one might have when studying the acceleration of reaction rates in aerosolized nano-and microdroplets.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to experiments, modelling the kinetics of reactions within droplets and at interfaces can help clarify our understanding of the mechanisms leading to reaction acceleration in micro-and nano-compartments. A few recent examples of such contributions include the kinetic modelling of reactions in microemulsions, 60 molecular dynamics simulations of a cycloaddition reaction at the water-graphene interface, 110 quantum mechanical calculations of the energies of desolvated molecules at the water-vacuum interface 61 and estimation of the magnitude of electric elds in microdroplets. 73 Finally, there is an important distinction between two different objectives that one might have when studying the acceleration of reaction rates in aerosolized nano-and microdroplets.…”
Section: Discussionmentioning
confidence: 99%
“…These rate coefficients will be sensitive to the molecular structure of the reactants, intermediates and products as well as additional compartment features such as solvent, electric elds and pH gradients that can alter reaction energetics and transition states at the interface. 23,52,53 Rate coefficients for adsorption and desorption, which also control surface reaction rates via interfacial concentration, will be similarly sensitive to the exact nature of the interface (i.e. liquid/vapor vs. oil/aqueous) as well as the solvent environment of the compartment.…”
Section: Discussionmentioning
confidence: 99%
“…There are many examples where nano-connement 20 of a small number of molecules or atoms has a profound inuence on physical and chemical properties; including the electronic structure of quantum dots and the transport and reactivity in carbon nanotubes, 21 zeolites, nanovessels, 22 metal organic frameworks, cells, etc. For these cases, compartmentalization produces properties and behavior not observed in their macroscopic analogs or described by continuum theories because connement is on the order of molecular/atomic dimensions, solvent correlation lengths 23,24 and/or is governed by stochastic uctuations of small numbers of molecules. [25][26][27][28][29] In contrast, it is not immediately obvious why connement of many, many millions of solute molecules in a micron-sized droplet or emulsion would produce behavior substantially different from what is observed in a beaker.…”
Section: Compartment Dimensions Concentrations and Characteristimentioning
confidence: 99%
“…In both natural and artificial nanometer-sized environments, confined water displays uniquely modified structure and dynamics with respect to the bulk liquid (15)(16)(17)(18). Recently, these modified properties were also found to have significant implications for the mechanism and energetics of reactions taking place in confined water with respect to those observed in bulk aqueous solution (19)(20)(21). In a pioneering study on supramolecular assemblies, Cram and collaborators (22) concluded that the interior of those cages is a "new and unique phase of matter" for the incarcerated guests.…”
mentioning
confidence: 99%